Ullmann coupling reactions on gold nanoparticles (Expanding the toolbox of organic synthesis) - Ukah, Nathaniel; Justus Liebig University Giessen (My University, 2024)
Ullmann coupling has proven to be a useful tool for constructing C−C bonds. However, the most prominent disadvantage of Ullmann coupling is the poor selectivity between homo and hetero-Ullmann products. In 2021, the research groups of Wegner and Schirmeisen found a breakthrough towards solving this long-standing problem, using organic on-surface synthesis. However, be it as good as it may seem, this technique is limited to surfaces with flat geometries to enable visualization of single molecules using Atomic Force Microscope (AFM). This stringent requirement limited the availability of the coupled products to few molecules, which is far less than that obtained via traditional in-solution Ullmann coupling. Therefore, in this work, and in analogy to the ultra-high vacuum on-surface synthesis, a new strategy for conducting organic reactions is developed. This strategy translates the 2D on-surface synthesis into 3D on-surface synthesis, adopts the high degree of selectivity obtained from 2D organic on-surface synthesis and enables the synthesis of large amounts of molecules (relative to the well-known 2D on-surface syntheses). In addition, it also circumvents both disdavantages obtained from the previously outlined approaches in Ullmann reactions. This developed strategy involves attaching the coupling unit (in the form of a ligand) to a 3D gold surface, to form a hybrid material, bearing the catalyst and the reacting partner, all combined in one entity. The adopted geometry of these ligands on a 3D gold surface was exploited in swapping the natural selectivity of Ullmann reaction, thus, favoring hetero over homo Ullmann coupling reactions. In a follow-up project, the different segments of the hybrid material were fine-tuned, and the binding group was changed from a 𝜋-donor ligand to a 𝜎-donor ligand. This changed the entire bonding strength to the Au surface, bonding geometry and chemical reactivity of the reacting molecules attached to the Au surface. Thus, enabling a transferrence of on-surface synthesis from 2D to 3D surface, while giving rise to enhanced selectivity towards intermolecular homo Ullmann reaction.
Keywords: ddc:540